Managing Change in a Malaysian Organisation: An Investigation into th effcets of Motivation and Leadership - Wan, Chee Hol (2007)
One of the biggest challenge facing today's organisations involves change management as the ultra-competitive market place requires leaders to often try to alter the way they do business. To successfully transform the organisations to meet their goals would entail strong leadership to bring about the change together with employees that understand and are motivated to undergo the change. However, traditionally all these functions are treated separately. In this study, the objective is to investigate the effects and the interactions between Malaysian organisation (Philips Lighting Malaysia), which has undergo major change programs over recent years and is facing issues related to leadership and employees' motivation This study employs a narratological approach to extract stories from members of the organisation through the use of in-depth interviews to create understanding of the interaction between the three functions. The findings of the study reveal that there exist complex relationships between managing change, motivation and leadership which are further complicated by additional elements such as corporate culture, leadership style, trust and organisational citizenship. These outcomes suggest that organisation and its management should adopt a holistic view when approaching change management;taking in consideration factors affecting employees’ motivation and the form of leadership needed to make it successful.